Addressing the impact of economic sanctions on Iranian drug shortages in the joint comprehensive plan of action: promoting access to medicines and health diplomacy. Issue 1 (December 2016) - Setayesh, Sogol; Mackey, Tim
Abstract Background The U.S Congress initiated sanctions against Iran after the 1979 U.S. Embassy hostage crisis in Tehran, and since then the scope of multilateral sanctions imposed by the United States, the European Union, and the United Nations Security Council have progressively expanded throughout the intervening years. Though primarily targeted at Iran's nuclear proliferation activities, sanctions have nevertheless resulted in negative public health outcomes for ordinary Iranian citizens. This includes creating vital domestic shortages to life-saving medicines, leaving an estimated 6 million Iranian patients with limited treatment access for a host of diseases. Sanctions have also crippled Iran's domestic pharmaceutical industry, leading to the disruption of generic medicines production and forcing the country to import medicines and raw materials that are of lower or questionable quality. Discussion Countries such as the United States have responded to this medical crisis by implementing export control exemptions with the aim of easing the trade of humanitarian goods (including certain pharmaceuticals and medical devices). However, despite these efforts, pharmaceutical firms and international banking institutions remain cautious about doing business with Iran, leaving the country faced with continuing shortages. We conducted a review of key characteristics of the Iranian drug shortage that identified 73 shortage drugs that closely tracked with the disease burden in the country. Additionally, 44 % of these drugs were also classified as essential medicines by the World Health Organization. A vast majority of these drugs were also covered under export control exemptions that theoretically should make them easier to procure, but nevertheless will still in shortage. Summary Based on our review of the sanctions regulatory framework and key characteristics of the Iranian drug shortage, we propose policy intervention leveraging the recently negotiated P5 + 1 agreement that begins the process of providing Iran relief from the international economic sanctions regime. This specifically includes advocating for the application of "health diplomacy" in ongoing multilateral negotiations following commencement of "implementation day, " by advocating for an additional set of reform measures incorporated into this historic negotiation that will finally address the humanitarian and medical crisis of drug shortages in Iran.